Predictive Relationship between Depression and Quality of Life among Patients with Type II Diabetes in Karachi-Pakistan - Umara Rauf; Uzma Ali (Journal of Basic & Applied Sciences, 2015)
The aim of the present study was to explore the relationship between depression and quality of life among individuals with type II diabetes. On the basis of literature review it was hypothesized that a) depression will predict quality of life among patients with diabetes b) there will be negative relationship between depression and quality of life among patients with diabetes. A purposive sample of 96 people with diabetes type II diagnosed by physicians was selected from different hospitals and different organizations of Karachi, Pakistan. Their age range was between 25 to 75 years (mean age = 41.2, SD = 12.3) and they belonged to three major socioeconomic status i.e. low, middle and high. To measure the depression Salma Siddiqui Depression Scale was used and quality of life was assessed through WHO Quality of life BREF-Urdu Version. Descriptive statistics and linear regression were applied for the analysis of data. Findings revealed that there was moderately significant negative relationship between Depression and Quality of Life (p<.000) and depression contributes 40% variance in quality of life among patients. The findings have clinical implications for general physicians and clinical psychologists as well as for the general population.